Involution of the uterus of dairy cattle - Edward P. Call (Kansas Agricultural Experiment Station Research Reports, 1989)
The rate of involution of the bovine uterus is remarkable. By 20 days after calving, tissue sloughing and hemorrhaging have ceased, and the size of the uterus has been reduced by more than 80%. By 40 days, the uterus has completely involuted except for isolated pockets of leukocytes. Any reproductive or metabolic disorders around calving will delay involution. A preventive herd health program (PHHP) including a reproductive examination of cows within a month after calving will pay dividends in improved reproductive performance. With a sound PHHP, servicing cows on the first heat after 42 days fresh is recommended.; Dairy Day, 1989, Kansas State University, Manhattan, KS, 1989; The 1989 Annual KSU Dairy Day is known as Dairy Day, 1989
Keywords: Dairy Day; 1989; Kansas Agricultural Experiment Station contribution; no. 90-140-S; Report of progress (Kansas Agricultural Experiment Station); 580; Dairy; Uterine involution; Preventive herd health program (PHHP)